2023
DOI: 10.1177/19458924221150977
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Olfactory Training as a Treatment for Olfactory Disorders Caused by Coronavirus Disease-2019: A Systematic Review and Meta-Analysis

Abstract: Background There have been reports investigating the use of olfactory training in olfactory dysfunction after COVID-19. Objective We evaluated the effect of olfactory training on the olfactory dysfunction of patients infected with COVID-19. Methods We searched PubMed, EMBASE, the Web of Science, the Cochrane database, SCOPUS, and Google Scholar up to May 2022. We retrieved studies that compared the extents of olfactory dysfunction before and after olfactory training. We performed a subgroup analysis by the dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Although some randomized control trials have demonstrated short-term benefits of using topical or oral corticosteroids, large-scale trials investigating their efficacy are yet to be conducted 48 . olfactory training have been shown to symptomatically improve olfactory dysfunction in both the acute and chronic phases 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Although some randomized control trials have demonstrated short-term benefits of using topical or oral corticosteroids, large-scale trials investigating their efficacy are yet to be conducted 48 . olfactory training have been shown to symptomatically improve olfactory dysfunction in both the acute and chronic phases 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Management of post-COVID-19 OD relies primarily on consistent olfactory training (OT), with several studies confirming the efficacy of OT for post-viral OD [49,50]. Given that an improvement in olfactory abilities into the normosmic range (i.e., the transient OD group in this study) appears to dampen the magnitude of BMI change, it is therefore important to support patients in adhering to olfactory training in an effort to restore the sense of smell and alleviate the effects of OD on BMI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that individuals with a full training compliance reported a better improvement of the sense of smell [133]. Several systematic reviews and meta-analyses have shown that OT is effective during both the acute phase of the infection and post-COVID-19 [134,135]. Steroids, systemic or intranasal, are also recommended in the context of sinonasal OD, having a good level of evidence [40,50].…”
Section: Neuroepithelial Mechanism Of Anosmia In Long Covid Patientsmentioning
confidence: 99%